Turkish pharmacy technicians' counseling practices and attitudes regarding emergency contraceptive pills - (:unkn) unknown (ACADEMIC JOURNALS, 2011)
Supplying emergency contraception pills through community pharmacies without the need for a doctor's prescription is an important public health role for the pharmacy staff, as a way of reducing unwanted pregnancies and induced abortions. Therefore, we aimed to assess the Turkish pharmacy technicians' counseling practices and attitudes regarding emergency contraception pills. A survey tool which was structured to question pharmacy technicians' demography, professional experience, counseling practices and attitudes regarding emergency contraception pills was administered to pharmacy technicians at the end of the pharmacy technician certification program. The fully completed questionnaires (n=145) were further analyzed. Mean [SEM] age of the pharmacy technicians was 25.3 [0.4] years and majority (89%) of them were practicing in a community pharmacy. Despite their positive attitude towards the emergency contraception pills, pharmacy technicians were found to provide insufficient emergency contraception pill counseling to clients. We suggest that organization of continuing education programs on reproductive and sexual health and emergency contraception for the pharmacy technicians could help increase the quality of emergency contraception pill counseling provided by the pharmacy technicians.
Keywords: Emergency contraception pill; counseling; attitude; community pharmacy; pharmacy technician; HEALTH-CARE PROVIDERS; OVER-THE-COUNTER; HORMONAL CONTRACEPTION; SOUTH-AFRICA; KNOWLEDGE; DEREGULATION; PERCEPTIONS; EXPERIENCES; USERS